Voicing pain and suffering through linguistic agents: Nuancing Elaine Scarry's view on the inability to express pain. Issue 4 (December 2016) - Bustan, Smadar
Abstract This article examines the well-known though contested stance of Elaine Scarry regarding the inability to express our pain. Reviewing the problem shows that certain practices (scientific, judicial, medical) communicate the pain objectively. But when transmitting our pain becomes challenging, one important solution is found in Scarry's suggested use of linguistic agents. These agents represent the felt pain, whether in actual (a stabbing nail, an electric shock) or imaginative forms ('like a ball that keeps falling down on you'), enabling us to convey an otherwise unconceivable torturous experience. As elements distinguished from the hurting body, they create a spatial separation that produces the necessary distance for safely projecting the pain on to something other than oneself. Historians strongly criticize Scarry's 'ontological' account, but in drawing on experimental laboratory work for discussing this reality-conferring function of language, the article addresses clinicians, neuroscientists, and healthcare workers in order to expose new perspectives for pain research.